1994
DOI: 10.1073/pnas.91.15.7237
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of chromosomal rearrangements associated with the developmental mutations Ph, W19H, and Rw on mouse chromosome 5.

Abstract: We are studying the chromosomal structure of three developmental mutations, dint spotting (W), patch (Ph), and rump white (Rw) on mouse chromosome 5. These mutations are clustered in a region containing three genes encoding tyrosine kinase receptors (Kit, PdJfyu, and FRkl). Using probes for these genes and for a closely linked locus, D5Mn125, we esta hed a high-resolution physical map covering r2.8 Mb. The entire chromosomal segment mapped in this study is deleted in the W19H mutation. The map i tes the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 33 publications
1
24
1
Order By: Relevance
“…In summary, Kit expression is restricted to distinct cell types in which the Kit receptor functions. Studies of the mechanisms that control cell typespecific Kit expression are therefore of great significance.The Kit RTK is encoded at the white spotting (W) locus on mouse chromosome 5 in the vicinity of the RTKs PDGFR␣ and flk1 and comprises 21 exons contained in 70 kb (13,19,20,39,40). Many W mutations affecting Kit structure and function have been identified and characterized; the analysis of expression mutations has provided some insight into the mechanism of tissue-specific Kit expression.…”
mentioning
confidence: 99%
“…In summary, Kit expression is restricted to distinct cell types in which the Kit receptor functions. Studies of the mechanisms that control cell typespecific Kit expression are therefore of great significance.The Kit RTK is encoded at the white spotting (W) locus on mouse chromosome 5 in the vicinity of the RTKs PDGFR␣ and flk1 and comprises 21 exons contained in 70 kb (13,19,20,39,40). Many W mutations affecting Kit structure and function have been identified and characterized; the analysis of expression mutations has provided some insight into the mechanism of tissue-specific Kit expression.…”
mentioning
confidence: 99%
“…22 and this publication). The proximal breakpoint of the Rw inversion lies centromeric to the En2 locus, whereas the distal breakpoint maps to the region between the Kit and Pdgfra genes in the central portion of the chromosome (14,22). These studies suggested that the dominant pigmentation defect in Rw also could be attributed to the long range effect on Kit expression in melanocyte precursors (14,19).…”
mentioning
confidence: 99%
“…The role of Kit in the intracellular signal transduction pathways in many distinct cell types is reflected by the pleiotropic affect of W on primordial germ cells, hematopoietic cells, melanocytes, and interstitial cells of Cajal in the small intestine, (9,10). The Ph mutation is associated with a deletion encompassing another receptor tyrosine kinase gene, Pdgfra (11)(12)(13)(14). Homozygous Ph͞Ph mice die between embryonic day (E) 9 and E 16 and show severe morphological anomalies (11,15), with some but not all anomalies observed in embryos with the targeted null-mutation for PDGF␣R (16).…”
mentioning
confidence: 99%
“…Rw is a large inversion terminating just upstream of Kit, and so may affect Kit expression (Nagle et al 1994), although expression is not lost . However, there is still no molecular information on rs.…”
Section: Introductionmentioning
confidence: 99%